PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PAPAN MULTIFUNGSI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS V SD NEGERI 101910 SIDODADI - Yolanda Patricia Panjaitan; Patri Janson Silaban; Irmina Pinem; Juliana; Eka Margareta Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by a multifunction board media on mathematics learning outcomes of fifth-grade students at SD Negeri 101910 Sidodadi in the 2024/2025 academic year, focusing on the topic of Greatest Common Factor (GCF) and Least Common Multiple (LCM). The research employed a quantitative experimental method with a sample of 35 students. Data collection techniques included pre-tests, post-tests, and questionnaires. The results showed that the students’ average pre-test score was 29.17, categorized as "needs guidance." After the implementation of the PBL model, the post-test average increased significantly to 80.46, categorized as "good." Data were tested using normality and hypothesis testing (t-test), which revealed that tcount (10.291) ≥ ttable (2.034), indicating a significant effect of the PBL model on student learning outcomes. Additionally, the correlation coefficient of 0.829 ≥ 0.334 indicated a strong relationship, with the PBL model contributing 85% to the learning outcomes. Thus, it can be concluded that the Problem Based Learning model assisted by multifunction board media is effective in improving fifth-grade students’ mathematics learning outcomes. This model can serve as an innovative and relevant teaching strategy to enhance conceptual understanding in elementary mathematics education.